Data investigation: Issues of data quality and implementing base analysis technique to evaluate quality of data in heterogeneous databases - Azwa, Abdul Aziz; Julaily Aida, Jusoh; Md Yazid, Mohamad Saman (2012)
Data investigation is a process to understand the nature of data in heterogeneous databases. Many organizations are using online transactions systems to support their company operations. The diversity of applications system that used to support organization may lead to data anomalies without the system owners realized the negative impact of decision making from insufficient information of data. The quality of the results from any analysis is only as good as the quality of the inputs (the data) that feed that analysis. Therefore, data quality process is still a major factor in the successful operation of IT. An introducing of new tech systems such as grid systems, ETL applications, semantic web are meaningless if data are lack of quality. In avoiding "Garbage In Garbage Out" principle, we proposed a technique that help to understand a natured of data which we refer as Base Analysis Technique (BAT). BAT is used to profile heterogeneous data in a structured approach, with the intention to determine abnormal data. The technique contains three levels of analysis consists of Top Level Analysis, Middle Level Analysis and Low Level Analysis. On the other hand, Data Quality Analysis System (DC/AS) is a tool that developed using open source technologies which is connected to commercial databases in supporting BAT to be implemented in three-tier architecture. This paper describes issues surrounding data quality area and how BAT evaluates the quality of data in heterogeneous databases. 2005 - 2012 JATIT & LLS. All rights reserved.